The Effect of Thyme Essential Oil on Liver Injuries Caused by Renal Ischemia-Reperfusion in Rats. (26th October 2022) - Rostami, Reza; Eslamifar, Zahra; Nazemi, Sedighe; Hosseini, Seyedeh Zeinab; Behvandi, Mohammad mehdi; Jafaripour, Leila
Abstract : Liver damage occurs following renal ischemia-reperfusion (RIR) that can cause inflammation and inflammatory cytokines activated after kidney injury. In this study, thyme essential oil (TE) with antioxidant and anti-inflammatory properties was used to reduce liver damage induced by renal IR. 32 male rats were randomly divided into 4 equal groups: (1) control, (2) RIR, (3) RIR+TE, and (4) TE. Rats received TE as a pretreatment at a dose of 0.5 ml/kg for one week. Then, under anesthesia for 45 minutes for ischemia, the kidneys of the animals were closed with clamps, and reperfusion was performed for 24 hours. Animal serum was isolated to evaluate alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) parameters. The liver of rats was examined for the measurement of malondialdehyde (MDA), nitric oxide (NO), glutathione (GSH), glutathione peroxidase (GPX), catalase (CAT), and expression of genes such as interleukin-6 (IL-6), tumor necrosis factor- α (TNF- α ), and caspase-3. ALP, AST, ALT, MDA, NO, IL-6, TNF- α, and caspase-3 increased significantly in the RIR group compared to the control group (p < 0.05 ). GSH, GPX, and CAT decreased significantly in the RIR group compared to the control group (p < 0.05 ). TE caused a decrease in ALP, AST, ALT, MDA, NO, IL-6, and TNF- α compared to the RIR group and caused an increase in the amount of GSH, GPX, and CAT in the RIR group (p < 0.05 ). This study showed that TE has antioxidant and anti-inflammatory properties that reduce liver damage induced by RIR.